Importance of the El Niño Teleconnection to the 21st Century California Wintertime Extreme Precipitation Increase. Issue 19 (10th October 2018) - Zecca, Katherina; Allen, Robert J.; Anderson, Ray G.
Abstract: Under continued climate warming, California (CA) hydrological projections, particularly precipitation, exhibit significant uncertainty. Recent analyses, however, have indicated a tendency for increased CA precipitation through the 21st century, particularly during December‐January‐February (DJF). Here we show that this increase is due entirely to an increase in extreme (>90th percentile) daily precipitation. This response is consistent with enhanced horizontal vapor transport off the CA coast, most of which is caused by thermodynamical effects due to increases in atmospheric moisture. Furthermore, observations over the late twentieth century show that CA DJF extreme precipitation is associated with an El Niño‐like sea surface temperature anomaly pattern. Models that better simulate the observed El Niño teleconnection with CA DJF precipitation also better reproduce the El Niño‐like sea surface temperature anomaly pattern associated with extreme precipitation, including the associated thermodynamical and dynamical atmospheric responses. In turn, these models simulate a significantly larger increase in extreme precipitation under warming. Plain Language Summary: In a warmer world, future California hydrological changes remain uncertain. Here we analyze state‐of‐the‐art model simulations and find an increase in California precipitation during the winter. Nearly all of this increase is due to an increase in extreme precipitation, associated with moistening of the warmer atmosphere. Moreover, models that better simulate the El Niño‐California precipitation teleconnection yield larger increases in extreme precipitation. This is related to better simulation of the dynamical and thermodynamical atmospheric responses associated with extreme California precipitation. Key Points: CMIP5 models project an increase in California wintertime extreme precipitation The bulk of the increase is due to moistening of the warmer atmosphere The responses are larger in models that better simulate the El Niño‐California precipitation teleconnection